Optimising the blended learning environment: the Arab Open University experience. (2nd January 2018) - Hamdi, Tahrir; Abu Qudais, Mohammed
Abstract: This paper will offer some insights into possible ways to optimise the blended learning environment based on experience with this modality of teaching at Arab Open University/Jordan branch and also by reflecting upon the results of several meta-analytical studies, which have shown blended learning environments to be more effective than their face to face and online only counterparts. Three key elements will be presented as important ways for improving the blended learning environment: forging genuine collaborative partnerships between institutions in terms of the team-writing of Open and Distance Learning (ODL) material, adopting a more theoretically based instructional approach, such as the cognitive apprenticeship (CA) model, which emphasises making thinking visible and developing a comprehensive understanding of blended education in order to help students achieve their educational goals.